2020
DOI: 10.29252/rbmb.9.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of (Sesc) for Easy Identification of Staphylococcus Epidermidis and Molecular and Phenotypic Study of Β-Lactam Resistance in Staphylococcus Epidermidis Isolates in Isfahan

Abstract: Background: Not only is it crucial to rapidly detect Staphylococcus epidermidis (S. epidermidis) isolates from a broad range of bacteria, but recognizing resistance agents can greatly improve current diagnostic and therapeutic strategies. Methods: The current cross-sectional study investigated 120 clinical isolates from a nosocomial S. epidermidis infection. The isolates were identified using common biochemical tests, and specific S. epidermidis surface protein C (SesC) primers were used to confirm the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Currently, the prevalence of S. epidermidis in Iran is reported to be about 27.8%–58.8% according to the sample type, sampling methods, diagnosis methods, and study objectives ( 12 , 14 , 21 ), and until recent years, various studies have reported an increase in resistance to methicillin in this species. The current systematic review and meta-analysis also reports the decline of MRSE infection frequency in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the prevalence of S. epidermidis in Iran is reported to be about 27.8%–58.8% according to the sample type, sampling methods, diagnosis methods, and study objectives ( 12 , 14 , 21 ), and until recent years, various studies have reported an increase in resistance to methicillin in this species. The current systematic review and meta-analysis also reports the decline of MRSE infection frequency in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Enterococci can grow in environments with high salt concentrations and temperatures of 10 to 45 °C. Several reports have documented that Staphylococcus epidermidis and Staphylococcus aureus and the two most important species enterococcus are among the leading causes of opportunistic human infections, 51 including urinary tract infections, infections of the surgical site and burn wound infections, bacteremia and sepsis, endocarditis, and others (1)(2)(3)(4)(5)(6)(7)(8). The microorganism first appeared in Europe in 1986 and then spread to the United States in 1998, with a 20-fold increase in nosocomial infections between 1989 and 1998 (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%